Obtenção de espécies de Lactobacillus microencapsulado em carragena com combinação proteica e aplicação em salame tipo milano - Biasuz, Thais (2018)
The objective of this study was to microencapsulate by drying in spray dryer (flow rate of 0.6 mL/min at 84 °C) species of Lactobacillus, L. rhamnosus. L. plantarum e L.paracasei in carrageenan and a blend of rice bran protein (RBP) and bovine serum albumin (BSA),followed by application in Milano-type Salami. Initially, a full factorial design using only L. rhamnosus to evaluate the effects of RBP/BSA concentration (1:1) (1.5% to 2.5%, m/v) and L. rhamnosus (0.6% to 1,4%, m/v) in encapsulation efficiency (EE). The concentration of carrageenan (0.5%, m/v) and Tween-80 was fixed in all runs. The microcapsules obtained were characterized as to their morphological, physical, thermal and chemical properties and viability of microorganism in digestibility. The microcapsules were validated in the proportion of RPB:BSA (1.5% m/v) and L. rhamnosus (0.6% m/v). Subsequently, in the same proportion were microencapsulated L. plantarum and L. paracasei subsp. paracassuggesting that the solubilization of part of the capsules occurred at the intestinal level, promoting protection of the microorganism. The analyzes of sausage fermented produced indicate that the legislation is adequate for microbiological and centesimal parameters. The counts of lactic acid bacteria were 109 CFU g-1 and 1010 CFU g-1, and the salami with microcapsules of L. rhamnosus counted higher, maintained after the digestibility test. The application of the tetrahedral test for sensory analysis did not detect differences between the control and probiotic samples (p ≤ 0.05). The observed results indicate that in adequate proportions, (RBP/BSA: 1,5%, Microrganism: 0,6%), that the combination of CA, RBP and BSA are feasible for encapsulation of L. rhamnosus and L. plantarum. The application of microcapsules of L. rhamnosus in Sausage fermented type Milano contributed to a satisfactory count of probiotics, even after the digestibility processes, indicating the protective effect of the product.ei. Two formulations of sausage fermented (control and microcapsules of L. rhamnosus) had evaluated of compositioncentesimal, resistance to digestibility, microbiological, and sensorial quality. The results obtained for L. rhamnosus in the experimental planning the EE varied from 37.7% (RBP/BSA: 2.5%, L. rhamnosus: 1.6%) to 99.7% (RBP/BSA: 1.5%, L.rhamnosus: 0.6%) with significant positive effect curvature (p ≤ 0.05), indicating that in the studied range the tendency of a point of maximum EE was observed, in contrast, the terms concentration of RBP/BSA, concentration of L. rhamnosus and their interaction term had significant negative effect. For L. plantarum and L. paracasei were microencapsulate with EE values of 99.5 to 99.8% and 77 to 79.5%, respectively. The thermal analyzes and FTIR-UART morphological of the microcapsules detected a protective effect on the L. rhamnosus. In the digestibility test, a decrease of 2 log CFU g-1 was observed in all the tests when compared to the count of microcapsules not submitted to the digestion process. The gastric count observed in all trials was lower than the intestinal count, suggesting that the solubilization of part of the capsules occurred at the intestinal level, promoting protection of the microorganism. The analyzes of sausage fermented produced indicate that the legislation is adequate for microbiological and centesimal parameters. The counts of lactic acid bacteria were 109 CFU g-1 and 1010 CFU g-1, and the salami with microcapsules of L. rhamnosuscounted higher, maintained after the digestibility test. The application of the tetrahedral test for sensory analysis did not detect differences between the control and probiotic samples (p ≤ 0.05). The observed results indicate that in adequate proportions, (RBP/BSA: 1,5%, Microrganism: 0,6%), that the combination of CA, RBP and BSA are feasible for encapsulation of L. rhamnosus and L. plantarum. The application of microcapsules of L. rhamnosus in Sausage fermented type Milano contributed to a satisfactory count of probiotics, even after the digestibility processes, indicating the protective effect of the product.